Cardiovascular risk in rheumatoid arthritis: assessment, management and next steps. (June 2016) - Zegkos, Thomas; Kitas, George; Dimitroulas, Theodoros
Rheumatoid arthritis (RA) is associated with increased cardiovascular (CV) morbidity and mortality which cannot be fully explained by traditional CV risk factors; cumulative inflammatory burden and antirheumatic medication-related cardiotoxicity seem to be important contributors. Despite the acknowledgment and appreciation of CV disease burden in RA, optimal management of individuals with RA represents a challenging task which remains suboptimal. To address this need, the European League Against Rheumatism (EULAR) published recommendations suggesting the adaptation of traditional risk scores by using a multiplication factor of 1.5 if two of three specific criteria are fulfilled. Such guidance requires proper coordination of several medical specialties, including general practitioners, rheumatologists, cardiologists, exercise physiologists and psychologists to achieve a desirable result. Tight control of disease activity, management of traditional risk factors and lifestyle modification represent, amongst others, the most important steps in improving CV disease outcomes in RA patients. Rather than enumerating studies and guidelines, this review attempts to critically appraise current literature, highlighting future perspectives of CV risk management in RA.